Ius Constituendum Pengujian Formil Dalam Perubahan Konstitusi - Prasetio, Dicky Eko; Widodo, Hananto (Fakultas Syariah INSURI Ponorogo, 2022)
Constitutional changes are part of the political and legal dynamics of a country. Changes to the constitution aim to meet the legal demands and needs of the community so that they are clearly and firmly regulated in the constitution. This paper is oriented towards the idea of a formal review of constitutional changes in Indonesia. This research is a normative legal research. The approach used in this research is a conceptual approach, a comparative approach, and a statutory approach. The primary legal materials in this study include the text of the 1945 Constitution of the Republic of Indonesia, constitutional texts in various countries and the Constitutional Court Decision No. 91/PUU-XVIII/2020. Secondary legal materials include: books, journal articles, and websites related to the constitution and constitutional law. Non-legal materials include legal dictionaries. The results of the study indicate that a formal review of constitutional changes is needed as an effort to maintain the supremacy of the constitution, including also placing the court's function as guardians of the law and the constitution in dealing with the determination of non-legal aspects in constitutional changes